A simple plan [videorecording (DVD)] - Raimi, Sam; Paxton, Bill; Thornton, Billy Bob; Fonda, Bridget; Briscoe, Brent (Paramount, 1999)
Two brothers and a friend find a corpse and a bag of money in a Minnesota woods. They decide to keep the money a secret from the police but this eventually results in deceit, mistrust and then murder.